Hybrid moulds with epoxy-based composites : effects of materials and processing on shrinkage and warpage - Martinho, P. G. (2011)
This paper contributes with the analysis of the case of a complex three-dimensional shape that was moulded in a standard steel mould and an alternative hybrid mould with steel cavity and epoxy-based composites cores. The mouldings were produced in semicrystalline and amorphous polymers. Pressure and temperature were recorded at two locations in the cavity. The processing conditions were simulated. The effect of the processing was observed on some dimensions of the part that were used for assessment of the shrinkage and warpage. The results suggest the importance of predicting the regime mould temperature when low thermal conductivity materials are used in moulding blocks. Results also evidenced that in hybrid moulds with resin blocks the shrinkage of the mouldings is a consequence of the specific polymer shrinkage and the deformation of the non-metallic core deformed by the processing pressure. The warpage occurring on these parts is also larger in comparison with conventional steel moulds.